Negative perception of teacher`s work as obstruction of school - parent non-conflict cooperation = Negatywna percepcja pracy nauczyciela jako przeszkoda bezkonfliktowej współpracy pomiędzy szkołą a rodzicem - Čiuladiene, Gražina; Valantinas, Antanas; Katkoniene, Agata (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Parental involvement has a positive impact on children`s learning achievement, school attendance etc. There is a lack of research of the parental involvement in school life extent, it?s advantages and obstacles in Lithuania.
Keywords: zaangażowanie rodziców; skargi rodziców; Litwa; Narodowa Agencja ds. Oceny Szkół; parental involvement; parents` complains; Lithuania; National Agency for School Evaluation